Cinnamaldehyde derivatives act as antimicrobial agents against Acinetobacter baumannii through the inhibition of cell division - Chai, Wern Chern; Whittall, Jonathan J.; Polyak, Steven W.; Foo, Klyie; Li, Xin; Dutschke, Cameron J.; Ogunniyi, Abiodun D.; Ma, Shutao; Sykes, Matthew J.; Semple, Susan J.; Venter, Henrietta (Frontiers in Microbiology, 2022)
Acinetobacter baumannii is a pathogen with high intrinsic antimicrobial resistance while multidrug resistant (MDR) and extensively drug resistant (XDR) strains of this pathogen are emerging. Treatment options for infections by these strains are very limited, hence new therapies are urgently needed. The bacterial cell division protein, FtsZ, is a promising drug target for the development of novel antimicrobial agents. We have previously reported limited activity of cinnamaldehyde analogues against Escherichia coli. In this study, we have determined the antimicrobial activity of six cinnamaldehyde analogues for antimicrobial activity against A. baumannii. Microscopic analysis was performed to determine if the compounds inhibit cell division. The on-target effect of the compounds was assessed by analysing their effect on polymerization and on the GTPase activity of purified FtsZ from A. baumannii. In silico docking was used to assess the binding of cinnamaldehyde analogues. Finally, in vivo and in vitro safety assays were performed. All six compounds displayed antibacterial activity against the critical priority pathogen A. baumannii, with 4-bromophenyl-substituted 4 displaying the most potent antimicrobial activity (MIC 32 µg/mL). Bioactivity was significantly increased in the presence of an efflux pump inhibitor for A. baumannii ATCC 19606 (up to 32-fold) and significantly, for extensively drug resistant UW 5075 (greater than 4-fold), suggesting that efflux contributes to the intrinsic resistance of A. baumannii against these agents. The compounds inhibited cell division in A. baumannii as observed by the elongated phenotype and targeted the FtsZ protein as seen from the inhibition of polymerisation and GTPase activity. In silico docking predicted that the compounds bind in the interdomain cleft adjacent to the H7 core helix. Di-chlorinated 6 was devoid of haemolytic activity and cytotoxicity against mammalian cells in vitro, as well as adverse activity in a Caenorhabditis elegans nematode model in vivo. Together, these findings present halogenated analogues 4 and 6 as promising candidates for further development as antimicrobial agents aimed at combating A. baumannii. This is also the first report of FtsZ-targeting compounds with activity against an XDR A. baumannii strain.